If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+(X-3)+(X-65)=200
We move all terms to the left:
X+(X-3)+(X-65)-(200)=0
We get rid of parentheses
X+X+X-3-65-200=0
We add all the numbers together, and all the variables
3X-268=0
We move all terms containing X to the left, all other terms to the right
3X=268
X=268/3
X=89+1/3
| m/3=6;m=18 | | 25=k5;k= | | f+15=9;f= | | 46=14+x;x= | | 7y=56;y= | | 200x+1000(x-3)+250(x-3)=5000 | | 7y=56;y | | x-9=23;x= | | 2/5(x+5/2)=20 | | 10x+5x-10=110 | | x∙1/5=60 | | 9(w+16)= | | 4x+3+8=36 | | 15x+6(180-x)=(180) | | 9+4v-11v=18-7v | | −5x+3(x+5)=1 | | 9(w+16)=–18 | | 3x/4-6=-9 | | 2e–8=10 | | 7n-4=2(n+2)-3n | | 14s+15=15 | | 18=-12-3a | | -3(2d+8)=-6-3-6d | | -8-7a=27 | | 3(2x+6)=5(x+6) | | -b+10=8 | | –2r–3=9 | | x/10+6=36 | | 20-10w=-9w-18+w | | 0.10(68-y)+0.5y=6 | | 13g-7(2g+10)=-g+14 | | 2x+12=3(x-3) |